A continuous composite reaction method of potassium sorbate

CN117772088BActive Publication Date: 2026-10-30NINGBO WANGLONG TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311731217.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2026-10-30
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

但是,活性炭的吸附效率不高,部分杂质容易从活性炭上脱附,混入山梨酸钾溶液中被共同干燥制得产品,影响到山梨酸钾的质量,故有待改善

Benefits of technology

1.活性炭微球树脂具有丰富的孔隙结构和良好的吸附效率,能够有效去除山梨酸钾溶液中的重金属离子、卤素离子和有机物,提升山梨酸钾产品的纯度和质量;树脂基体和活性炭微球之间可以协同作用,吸附的杂质从树脂基体或是活性炭微球上发生脱附时,另一组分可以迅速的捕获吸附杂质分子,减少杂质分子脱附现象的发生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a continuous composite reaction method of potassium sorbate, which comprises the following steps: dissolving sorbic acid in a solvent to obtain a sorbic acid solution, adding a potassium hydroxide aqueous solution into the sorbic acid solution to stir to obtain a reaction liquid, controlling the pH value of the reaction liquid, obtaining a potassium sorbate aqueous solution after reaction; controlling the temperature of the potassium sorbate aqueous solution, filtering the potassium sorbate aqueous solution through activated carbon microsphere resin to obtain a filtered potassium sorbate solution; cooling and drying the filtered potassium sorbate solution to obtain a potassium sorbate finished product; the activated carbon microsphere resin comprises a resin matrix and activated carbon microspheres, and the resin matrix comprises the following components in mass fractions: 10-20 parts of cationic modified lignin, 40-50 parts of butyl acrylate, 30-40 parts of dimethyl glycol acrylate and 3-7 parts of an initiator. The application has the effects of improving the product quality of potassium sorbate, improving the drying effect and reducing the impurity content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of potassium sorbate preparation, and in particular to a continuous composite reaction method for potassium sorbate. Background Technology

[0002] Potassium sorbate, scientifically known as potassium 2,4-hexadienoate, has strong antibacterial and bactericidal effects. It is a highly effective and low-toxicity preservative that inhibits yeast, mold, and many fungi. It is widely used in human food, animal feed, cosmetics, pharmaceuticals, packaging materials, and rubber additives.

[0003] The existing potassium sorbate preparation process involves a chemical reaction between solid sorbic acid and an aqueous solution of potassium hydroxide. Activated carbon is then used to adsorb and remove pigments and impurities, followed by spray drying to obtain the potassium sorbate product. The content of heavy metal ions, halide ions, and organic matter affects the quality and safety of the potassium sorbate product. Filtration is an important means of improving the quality of potassium sorbate products, and related technologies typically use activated carbon slurry to adsorb impurities from the potassium sorbate solution. However, the adsorption efficiency of activated carbon is not high, and some impurities easily desorb from the activated carbon and mix into the potassium sorbate solution, being dried together with the product and affecting its quality. Therefore, improvements are needed. Summary of the Invention

[0004] To improve the quality of potassium sorbate products, this application provides a continuous composite reaction method for potassium sorbate.

[0005] The continuous composite reaction method for potassium sorbate provided in this application adopts the following technical solution: A method for continuous composite reaction of potassium sorbate, characterized by comprising the following steps: (1) Sorbic acid is dissolved in a solvent to obtain a sorbic acid solution. Potassium hydroxide aqueous solution is added to the sorbic acid solution and stirred to obtain a reaction solution. The pH value of the reaction solution is controlled. After the reaction, potassium sorbate aqueous solution is obtained. (2) Control the temperature of potassium sorbate aqueous solution and filter the potassium sorbate aqueous solution through activated carbon microsphere resin to obtain the filtered potassium sorbate solution. (3) After cooling the filtered potassium sorbate solution, dry it to obtain the finished potassium sorbate product; The activated carbon microsphere resin comprises a resin matrix and activated carbon microspheres, wherein the resin matrix comprises the following components in parts by weight: 10-20 parts of cationic modified lignin 40-50 parts of butyl acrylate 30-40 parts of ethylene glycol dimethacrylate Initiator 3-7 parts.

[0006] Activated carbon microsphere resin possesses abundant pore structure and excellent adsorption efficiency, effectively removing heavy metal ions, halide ions, and organic matter from potassium sorbate solution, thus improving the purity and quality of potassium sorbate products. Cationic modified lignin exhibits better positive charge, resulting in superior adsorption performance of the activated carbon microsphere resin. The resin matrix obtained by polymerizing butyl acrylate and ethylene glycol dimethacrylate using an initiator possesses a three-dimensional porous structure, exhibiting advantages such as high stability, large specific surface area, and high adsorption capacity. The open pore structure of the activated carbon microspheres allows for full contact with the filtrate, resulting in low resistance during filtrate passage and excellent adsorption performance. The resin matrix and activated carbon microspheres can work synergistically; when adsorbed impurities desorb from either the resin matrix or the activated carbon microspheres, the other component can rapidly capture the adsorbed impurity molecules, reducing the occurrence of impurity molecule desorption.

[0007] Preferably, the cationic modified lignin includes quaternary ammonium salt modifiers and hydroxypropylated lignin.

[0008] Quaternary ammonium salt modifiers modify hydroxypropylated lignin by attaching quaternary ammonium salt groups to its surface, enhancing its positive charge and promoting the formation of porous structures in activated carbon microsphere resin. The quaternary ammonium salt groups, through electrostatic interactions, facilitate the adsorption of negatively charged impurities such as halide ions, improving the adsorption performance of activated carbon microsphere resin, reducing the product's hygroscopicity, and enhancing the drying effect of potassium sorbate products. Hydroxypropylated lignin possesses abundant hydroxyl, methoxy, and carbonyl structures, which can serve as binding sites for heavy metals, forming lignin-metal chelates with excellent adsorption performance for heavy metal ions.

[0009] Preferably, the mass ratio of the quaternary ammonium salt modifier to the hydroxypropylated lignin is (0.1-0.15):1.

[0010] The activated carbon microsphere resin obtained according to the above mass ratio has good adsorption performance.

[0011] Preferably, the quaternary ammonium salt modifier includes epichlorohydrin and tetramethylethylenediamine.

[0012] The three-membered ring of the epoxy group in epichlorohydrin has high stress and is prone to ring-opening reaction with natural polymers containing active groups such as hydroxyl or amino groups under acid or base catalysis. The quaternary ammonium salt modifier obtained by reacting epichlorohydrin and tetramethylethylenediamine has a double epoxy structure. The high reactivity of the epoxy group can be used to introduce the quaternary ammonium salt modifier into the polymer structure to obtain materials with good adsorption properties.

[0013] Preferably, the activated carbon microspheres are prepared using the following steps: Polyvinylpyrrolidone, glycidyl methacrylate and azobisisobutyronitrile were mixed to obtain a mixed solution. The mixed solution was sonicated and then inert gas was introduced to remove oxygen. The ultrasonically deoxygenated mixed solution was then rotary evaporated to carry out the reaction. The mixed solution after the reaction was centrifuged to obtain a precipitate. The precipitate was washed and dried to obtain glycidyl methacrylate seed particles. Glycidyl methacrylate seed particles were activated to obtain a seed particle suspension. Glycidyl methacrylate, trimethylolpropane trimethacrylate and a pore-forming agent were mixed to obtain an oil phase. Sodium dodecyl sulfate and polyvinylpyrrolidone were mixed into deionized water to obtain an aqueous phase. The oil phase was added to the aqueous phase and emulsified to obtain an emulsion. Benzoin dimethyl ether and the emulsion were added to the activated seed particle suspension. The mixture was stirred under light-protected conditions to obtain a polymerization solution. The stirred polymerization solution was reacted under ultraviolet light irradiation. The polymer solution was centrifuged and washed to obtain polymer microspheres. The polymer microspheres were carbonized at high temperature to obtain carbonized microspheres. The carbonized microspheres were then heated further and water vapor was introduced to carry out a second carbonization reaction. After cooling, activated carbon microspheres were obtained.

[0014] The activated carbon microspheres prepared according to the above method have special morphology and asymmetry. Because the polymer used in the synthesis has both hydrophilic and lipophilic properties, the activated carbon microspheres have a dual nature and can adsorb both hydrophilic and lipophilic impurity molecules at the same time. Through chemical bonding with organic matter in the filtrate, they have better adsorption capacity and filtration efficiency, which helps to improve the quality of potassium sorbate products.

[0015] Preferably, the temperature for the first carbonization of the polymer microspheres is 300-400℃, and the temperature for the second carbonization is 600-700℃.

[0016] The potassium sorbate byproduct obtained by reacting under the above conditions has high purity and good quality.

[0017] Preferably, the pore-forming agent is p-xylene and dodecanol.

[0018] The binary porogen obtained by combining p-xylene and dodecyl alcohol can help activated carbon microspheres form a better pore structure. p-xylene is a non-polar porogen, while dodecyl alcohol is a polar porogen. The two swell polymer monomers in oil and aqueous solutions, respectively, promoting the formation of microporous structures and improving the morphology of activated carbon microspheres. The resulting activated carbon microspheres have a large specific surface area.

[0019] Preferably, the mass ratio of p-xylene to dodecanol is 1:(1-1.5).

[0020] The activated carbon microspheres obtained according to the above mass ratio have a good pore structure.

[0021] Preferably, the activated carbon microsphere resin is prepared using the following steps: A mixture of cationic modified lignin, butyl acrylate, ethylene glycol dimethacrylate and an initiator was prepared and reacted under heating and stirring conditions. The reacted mixture was washed and dried to obtain a resin matrix. A spinning solution is obtained by mixing a resin matrix, polyvinylidene fluoride, and polyethylene glycol. Activated carbon microspheres are dispersed in N,N-dimethylformamide to obtain an activated carbon microsphere suspension. The spinning solution and the activated carbon microsphere suspension are then subjected to coaxial electrospinning to obtain activated carbon microsphere resin.

[0022] The activated carbon microsphere resin prepared according to the above steps has a rich porous structure. The activated carbon microspheres are uniformly attached to the resin matrix fibers obtained by electrospinning. The activated carbon microspheres and resin matrix fibers work synergistically to more efficiently adsorb impurities and pigments in the filtrate, improve the adsorption performance of the activated carbon microsphere resin, increase the purity of the potassium sorbate solution, and thus improve the drying effect and quality of the potassium sorbate product.

[0023] Preferably, the temperature for filtration using activated carbon microsphere resin in step (2) is 55-65℃ and the filtration time is 40-60min.

[0024] By performing the filtration operation under the above conditions, activated carbon microsphere resin can efficiently adsorb impurities in potassium sorbate aqueous solution, resulting in a high-quality potassium sorbate product.

[0025] In summary, this application includes at least one of the following beneficial technical effects: 1. Activated carbon microsphere resin has abundant pore structure and good adsorption efficiency, which can effectively remove heavy metal ions, halide ions and organic matter from potassium sorbate solution, and improve the purity and quality of potassium sorbate product; the resin matrix and activated carbon microspheres can work synergistically. When the adsorbed impurities desorb from the resin matrix or activated carbon microspheres, the other component can quickly capture the adsorbed impurity molecules, reducing the occurrence of impurity molecule desorption.

[0026] 2. The quaternary ammonium salt groups in cationic modified lignin help adsorb negatively charged impurities such as halide ions through electrostatic interactions, thereby improving the adsorption performance of activated carbon microsphere resin, reducing the hygroscopicity of the product, and enhancing the drying effect of potassium sorbate products.

[0027] 3. Activated carbon microsphere resin has stable properties and can be regenerated by washing with ethanol, allowing for repeated use and reducing the generation of solid waste. Detailed Implementation

[0028] This application discloses a method for a continuous composite reaction of potassium sorbate. The following detailed description is provided in conjunction with the embodiments: Example

[0029] Example 1 Preparation of porogens A porogen was obtained by mixing 4 kg of p-xylene (CAS No.: 106-42-3) and 4 kg of dodecanol (CAS No.: 112-53-8).

[0030] Preparation of activated carbon microspheres 2 kg of polyvinylpyrrolidone (CAS No.: 9003-39-8) was dissolved in a 10 L anhydrous ethanol-filled flask. 15 L of glycidyl methacrylate (CAS No.: 106-91-2) and 200 g of azobisisobutyronitrile (CAS No.: 78-67-1) were added to the flask. After sonication for 10 min, nitrogen gas was purged for about 30 min to remove oxygen. The flask was then reacted in a large rotary evaporator at 80 r / min at 70 °C for 12 h. The precipitate obtained by centrifugation of the reaction solution was washed three times with anhydrous ethanol and dried to obtain glycidyl methacrylate seed particles.

[0031] 10 kg of glycidyl methacrylate seed particles were activated in 50 kg of 0.2% sodium dodecyl sulfate (CAS No.: 151-21-3) aqueous solution for 15 min to obtain a seed particle suspension. 45 kg of glycidyl methacrylate, 30 kg of trimethylolpropane trimethacrylate (CAS No.: 3290-92-4) and 8 kg of pore-forming agent were mixed to obtain an oil phase. 0.1 kg of sodium dodecyl sulfate and 2.5 kg of polyvinyl alcohol (CAS No.: 25213-24-5) were mixed in 50 kg of deionized water to obtain an aqueous phase. The oil phase was then added to the aqueous phase, and the mixture was fully emulsified using a cell disruptor to form an oil-in-water emulsion. 0.3 kg of dialkoxyacetophenone and the emulsion were added to the activated seed particle suspension, and the mixture was stirred and swollen for 20 min under light-protected conditions. The stirred solution was then reacted under UV light for 2 h. The reacted solution was centrifuged and washed with ethanol to obtain polymer microspheres.

[0032] The polymer microspheres were heated to 300°C at a rate of 5°C / min under a nitrogen atmosphere and held for 10 h to obtain carbonized microspheres. The carbonized microspheres were then heated to 600°C at a rate of 5°C / min under nitrogen protection. After heating, water vapor was introduced at a flow rate of 12 mL / min and held for 2 h. After cooling, the polymer microspheres were obtained.

[0033] Preparation of cationic modified lignin 40 kg of epichlorohydrin (CAS No.: 106-89-8) and 8 kg of methanol were mixed in a constant-temperature reactor. Under stirring and nitrogen protection, the water circulation thermostat was turned on to maintain the system temperature at 20 °C. 5 kg of tetramethylethylenediamine (CAS No.: 110-18-9) was added to the epichlorohydrin at a uniform rate over 3 min. The reactor was sealed and stirred for 8 h. 20 L of petroleum ether was added to the reactor after the reaction under nitrogen protection. The reactor was sealed and allowed to stand for 30 min. The supernatant was then discarded. The above steps were repeated three times. The resulting product was placed in a vacuum dryer and dried at 30 °C for 8 h to obtain the quaternary ammonium salt modifier.

[0034] 11.1 kg of anhydrous glycerol (CAS No.: 556-52-5) and 21.1 kg of potassium hydroxide (CAS No.: 1310-58-3) were dispersed in 200 kg of acetone to obtain a catalyst solution. 35 kg of propylene oxide (CAS No.: 75-56-9), 40 kg of alkali lignin (CAS No.: 9005-53-2), and the catalyst solution were mixed and stirred evenly in a high-pressure reactor and kept at 150 °C for 2 h to obtain hydroxypropylated lignin. 27.3 kg of hydroxypropyl... Hydroxypropyl lignin was mixed with 40 L of 1% sodium hydroxide aqueous solution in a reactor and stirred at 50 °C for 2 h to activate the hydroxypropyl lignin. 2.7 kg of quaternary ammonium salt modifier was dissolved in 10 L of deionized water to obtain a modifier solution. The modifier solution was added to the reactor and stirred at 60 °C to carry out the reaction. The solution after reaction was centrifuged to obtain a precipitate. The precipitate was washed with deionized water and then placed in a freeze dryer cold trap for pre-freezing for 2 h. It was then vacuum freeze-dried at -60 °C for 6 h to obtain cationic modified lignin.

[0035] Preparation of activated carbon microsphere resin Under nitrogen protection, 10 kg of cationic modified lignin, 40 kg of butyl acrylate (CAS No.: 141-32-2), 30 kg of ethylene glycol dimethacrylate (CAS No.: 97-90-5) and 3 kg of azobisisobutyronitrile were mixed to obtain a mixture, which was reacted in a microwave high-pressure reactor at 75℃ for 15 min. The mixture after reaction was washed with ethanol and dried under vacuum at 50℃ for 6 h to obtain a resin matrix. 80 kg of resin matrix, 50 kg of polyvinylidene fluoride, and 80 kg of polyethylene glycol were mixed and dispersed to obtain a spinning solution. 10 kg of activated carbon microspheres were dispersed in 200 kg of N,N-dimethylformamide to obtain an activated carbon microsphere suspension. The spinning solution and the activated carbon microsphere suspension were coaxially electrospun. The syringe advance rate was 0.005 mm / s. The inner diameter of the inner nozzle of the coaxial nozzle was 0.4 mm and the outer diameter was 0.5 mm. The inner diameter of the outer nozzle was 0.9 mm and the outer diameter was 1 mm, resulting in activated carbon microsphere resin.

[0036] Preparation of potassium sorbate 10 kg of sorbic acid was dissolved in 100 kg of deionized water to obtain a sorbic acid solution. 3 kg of potassium hydroxide was dissolved in deionized water to obtain a potassium hydroxide aqueous solution. The potassium hydroxide aqueous solution was added to the sorbic acid solution and stirred to obtain a reaction solution. The pH of the reaction solution was controlled to be 9 by the amount of potassium hydroxide aqueous solution added. The reaction temperature was controlled to be 60℃. After reacting for 30 minutes, a potassium sorbate aqueous solution was obtained. The temperature of the potassium sorbate aqueous solution was controlled at 55℃, and the potassium sorbate aqueous solution was filtered through activated carbon microsphere resin for 40 minutes to obtain the filtered potassium sorbate solution. The filtered potassium sorbate solution was cooled and then sent to a spray dryer for spray drying at a temperature of 250°C to obtain the finished potassium sorbate product.

[0037] Example 2 Preparation of porogens A porogen was obtained by mixing 3.2 kg of p-xylene (CAS No.: 106-42-3) and 4.8 kg of dodecanol (CAS No.: 112-53-8).

[0038] Preparation of activated carbon microspheres 2 kg of polyvinylpyrrolidone (CAS No.: 9003-39-8) was dissolved in a 10 L anhydrous ethanol-filled flask. 15 L of glycidyl methacrylate (CAS No.: 106-91-2) and 200 g of azobisisobutyronitrile (CAS No.: 78-67-1) were added to the flask. After sonication for 10 min, nitrogen gas was purged for about 30 min to remove oxygen. The flask was then reacted in a large rotary evaporator at 80 r / min at 70 °C for 12 h. The precipitate obtained by centrifugation of the reaction solution was washed three times with anhydrous ethanol and dried to obtain glycidyl methacrylate seed particles.

[0039] 10 kg of glycidyl methacrylate seed particles were activated in 50 kg of 0.2% sodium dodecyl sulfate (CAS No.: 151-21-3) aqueous solution for 15 min to obtain a seed particle suspension. 45 kg of glycidyl methacrylate, 30 kg of trimethylolpropane trimethacrylate (CAS No.: 3290-92-4) and 8 kg of pore-forming agent were mixed to obtain an oil phase. 0.1 kg of sodium dodecyl sulfate and 2.5 kg of polyvinyl alcohol (CAS No.: 25213-24-5) were mixed in 50 kg of deionized water to obtain an aqueous phase. The oil phase was then added to the aqueous phase, and the mixture was fully emulsified using a cell disruptor to form an oil-in-water emulsion. 0.3 kg of dialkoxyacetophenone and the emulsion were added to the activated seed particle suspension, and the mixture was stirred and swollen for 20 min under light-protected conditions. The stirred solution was then reacted under UV light for 2 h. The reacted solution was centrifuged and washed with ethanol to obtain polymer microspheres.

[0040] The polymer microspheres were heated to 400℃ at a rate of 5℃ / min under a nitrogen atmosphere and held for 10h to obtain carbonized microspheres. The carbonized microspheres were then heated to 700℃ at a rate of 5℃ / min under nitrogen protection. After heating, water vapor was introduced at a flow rate of 12mL / min and held for 2h. After cooling, the polymer microspheres were obtained.

[0041] Preparation of cationic modified lignin 40 kg of epichlorohydrin (CAS No.: 106-89-8) and 8 kg of methanol were mixed in a constant-temperature reactor. Under stirring and nitrogen protection, the water circulation thermostat was turned on to maintain the system temperature at 20 °C. 5 kg of tetramethylethylenediamine (CAS No.: 110-18-9) was added to the epichlorohydrin at a uniform rate over 3 min. The reactor was sealed and stirred for 8 h. 20 L of petroleum ether was added to the reactor after the reaction under nitrogen protection. The reactor was sealed and allowed to stand for 30 min. The supernatant was then discarded. The above steps were repeated three times. The resulting product was placed in a vacuum dryer and dried at 30 °C for 8 h to obtain the quaternary ammonium salt modifier.

[0042] 11.1 kg of anhydrous glycerol (CAS No.: 556-52-5) and 21.1 kg of potassium hydroxide (CAS No.: 1310-58-3) were dispersed in 200 kg of acetone to obtain a catalyst solution. 35 kg of propylene oxide (CAS No.: 75-56-9), 40 kg of alkali lignin (CAS No.: 9005-53-2), and the catalyst solution were mixed and stirred evenly in a high-pressure reactor and kept at 150 °C for 2 h to obtain hydroxypropylated lignin. 26 kg of hydroxypropyl... Hydroxypropyl lignin was mixed with 40 L of 1% sodium hydroxide aqueous solution in a reactor and stirred at 50 °C for 2 h to activate the hydroxypropyl lignin. 4 kg of quaternary ammonium salt modifier was dissolved in 10 L of deionized water to obtain a modifier solution. The modifier solution was added to the reactor and stirred at 60 °C to carry out the reaction. The reacted solution was centrifuged to obtain a precipitate. The precipitate was washed with deionized water and then placed in a freeze dryer cold trap for pre-freezing for 2 h. It was then vacuum freeze-dried at -60 °C for 6 h to obtain cationic modified lignin.

[0043] Preparation of activated carbon microsphere resin Under nitrogen protection, 20 kg of cationic modified lignin, 50 kg of butyl acrylate (CAS No.: 141-32-2), 40 kg of ethylene glycol dimethacrylate (CAS No.: 97-90-5) and 7 kg of azobisisobutyronitrile were mixed to obtain a mixture, which was reacted in a microwave high-pressure reactor at 75 °C for 15 min. The mixture after reaction was washed with ethanol and then dried under vacuum at 50 °C for 6 h to obtain a resin matrix. 110 kg of resin matrix, 70 kg of polyvinylidene fluoride, and 110 kg of polyethylene glycol were mixed and dispersed to obtain a spinning solution. 10 kg of activated carbon microspheres were dispersed in 200 kg of N,N-dimethylformamide to obtain an activated carbon microsphere suspension. The spinning solution and the activated carbon microsphere suspension were subjected to coaxial electrospinning with a syringe feed rate of 0.005 mm / s. The inner nozzle of the coaxial nozzle had an inner diameter of 0.4 mm and an outer diameter of 0.5 mm, while the outer nozzle had an inner diameter of 0.9 mm and an outer diameter of 1 mm, resulting in activated carbon microsphere resin.

[0044] Preparation of potassium sorbate 10 kg of sorbic acid was dissolved in 100 kg of deionized water to obtain a sorbic acid solution. 3 kg of potassium hydroxide was dissolved in deionized water to obtain a potassium hydroxide aqueous solution. The potassium hydroxide aqueous solution was added to the sorbic acid solution and stirred to obtain a reaction solution. The pH of the reaction solution was controlled to be 9 by the amount of potassium hydroxide aqueous solution added. The reaction temperature was controlled to be 60℃. After reacting for 30 minutes, a potassium sorbate aqueous solution was obtained. The temperature of the potassium sorbate aqueous solution was controlled at 65℃, and the potassium sorbate aqueous solution was filtered through activated carbon microsphere resin for 60 minutes to obtain the filtered potassium sorbate solution. The filtered potassium sorbate solution was cooled and then sent to a spray dryer for spray drying at a temperature of 250°C to obtain the finished potassium sorbate product.

[0045] Example 3 Preparation of porogens A porogen was obtained by mixing 3.55 kg of p-xylene (CAS No.: 106-42-3) and 4.55 kg of dodecanol (CAS No.: 112-53-8).

[0046] Preparation of activated carbon microspheres 2 kg of polyvinylpyrrolidone (CAS No.: 9003-39-8) was dissolved in a 10 L anhydrous ethanol-filled flask. 15 L of glycidyl methacrylate (CAS No.: 106-91-2) and 200 g of azobisisobutyronitrile (CAS No.: 78-67-1) were added to the flask. After sonication for 10 min, nitrogen gas was purged for about 30 min to remove oxygen. The flask was then reacted in a large rotary evaporator at 80 r / min at 70 °C for 12 h. The precipitate obtained by centrifugation of the reaction solution was washed three times with anhydrous ethanol and dried to obtain glycidyl methacrylate seed particles.

[0047] 10 kg of glycidyl methacrylate seed particles were activated in 50 kg of 0.2% sodium dodecyl sulfate (CAS No.: 151-21-3) aqueous solution for 15 min to obtain a seed particle suspension. 45 kg of glycidyl methacrylate, 30 kg of trimethylolpropane trimethacrylate (CAS No.: 3290-92-4) and 8 kg of pore-forming agent were mixed to obtain an oil phase. 0.1 kg of sodium dodecyl sulfate and 2.5 kg of polyvinyl alcohol (CAS No.: 25213-24-5) were mixed in 50 kg of deionized water to obtain an aqueous phase. The oil phase was then added to the aqueous phase, and the mixture was fully emulsified using a cell disruptor to form an oil-in-water emulsion. 0.3 kg of dialkoxyacetophenone and the emulsion were added to the activated seed particle suspension, and the mixture was stirred and swollen for 20 min under light-protected conditions. The stirred solution was then reacted under UV light for 2 h. The reacted solution was centrifuged and washed with ethanol to obtain polymer microspheres.

[0048] The polymer microspheres were heated to 350°C at a rate of 5°C / min under a nitrogen atmosphere and held for 10 h to obtain carbonized microspheres. The carbonized microspheres were then heated to 650°C at a rate of 5°C / min under nitrogen protection. After heating, water vapor was introduced at a flow rate of 12 mL / min and held for 2 h. After cooling, the polymer microspheres were obtained.

[0049] Preparation of cationic modified lignin 40 kg of epichlorohydrin (CAS No.: 106-89-8) and 8 kg of methanol were mixed in a constant-temperature reactor. Under stirring and nitrogen protection, the water circulation thermostat was turned on to maintain the system temperature at 20 °C. 5 kg of tetramethylethylenediamine (CAS No.: 110-18-9) was added to the epichlorohydrin at a uniform rate over 3 min. The reactor was sealed and stirred for 8 h. 20 L of petroleum ether was added to the reactor after the reaction under nitrogen protection. The reactor was sealed and allowed to stand for 30 min. The supernatant was then discarded. The above steps were repeated three times. The resulting product was placed in a vacuum dryer and dried at 30 °C for 8 h to obtain the quaternary ammonium salt modifier.

[0050] 11.1 kg of anhydrous glycerol (CAS No.: 556-52-5) and 21.1 kg of potassium hydroxide (CAS No.: 1310-58-3) were dispersed in 200 kg of acetone to obtain a catalyst solution. 35 kg of propylene oxide (CAS No.: 75-56-9), 40 kg of alkali lignin (CAS No.: 9005-53-2), and the catalyst solution were mixed and stirred evenly in a high-pressure reactor and kept at 150 °C for 2 h to obtain hydroxypropylated lignin. 26.6 kg of hydroxypropyl... Hydroxypropyl lignin was mixed with 40 L of 1% sodium hydroxide aqueous solution in a reactor and stirred at 50 °C for 2 h to activate the hydroxypropyl lignin. 3.4 kg of quaternary ammonium salt modifier was dissolved in 10 L of deionized water to obtain a modifier solution. The modifier solution was added to the reactor and stirred at 60 °C to carry out the reaction. The solution after the reaction was centrifuged to obtain a precipitate. The precipitate was washed with deionized water and then placed in a freeze dryer cold trap for pre-freezing for 2 h. It was then vacuum freeze-dried at -60 °C for 6 h to obtain cationic modified lignin.

[0051] Preparation of activated carbon microsphere resin Under nitrogen protection, 15 kg of cationic modified lignin, 45 kg of butyl acrylate (CAS No.: 141-32-2), 35 kg of ethylene glycol dimethacrylate (CAS No.: 97-90-5) and 5 kg of azobisisobutyronitrile were mixed to obtain a mixture, which was reacted in a microwave high-pressure reactor at 75 °C for 15 min. The mixture after reaction was washed with ethanol and dried under vacuum at 50 °C for 6 h to obtain a resin matrix. A spinning solution was prepared by mixing and dispersing 90 kg of resin matrix, 55 kg of polyvinylidene fluoride, and 90 kg of polyethylene glycol. 10 kg of activated carbon microspheres were dispersed in 200 kg of N,N-dimethylformamide to obtain an activated carbon microsphere suspension. The spinning solution and the activated carbon microsphere suspension were then subjected to coaxial electrospinning with a syringe feed rate of 0.005 mm / s. The inner nozzle of the coaxial nozzle had an inner diameter of 0.4 mm and an outer diameter of 0.5 mm, while the outer nozzle had an inner diameter of 0.9 mm and an outer diameter of 1 mm, resulting in activated carbon microsphere resin.

[0052] Preparation of potassium sorbate 10 kg of sorbic acid was dissolved in 100 kg of deionized water to obtain a sorbic acid solution. 3 kg of potassium hydroxide was dissolved in deionized water to obtain a potassium hydroxide aqueous solution. The potassium hydroxide aqueous solution was added to the sorbic acid solution and stirred to obtain a reaction solution. The pH of the reaction solution was controlled to be 9 by the amount of potassium hydroxide aqueous solution added. The reaction temperature was controlled to be 60℃. After reacting for 30 minutes, a potassium sorbate aqueous solution was obtained. The temperature of the potassium sorbate aqueous solution was controlled at 60℃, and the potassium sorbate aqueous solution was filtered through activated carbon microsphere resin for 50 minutes to obtain the filtered potassium sorbate solution. The filtered potassium sorbate solution was cooled and then sent to a spray dryer for spray drying at a temperature of 250°C to obtain the finished potassium sorbate product.

[0053] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that the amount of p-xylene used in Example 4 is 5.33 kg and the amount of dodecanol used is 2.67 kg.

[0054] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that the mass of p-xylene is 2.67 kg and the mass of dodecanol is 5.33 kg in Example 5.

[0055] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that the mass of the quaternary ammonium salt modifier in Example 6 is 2 kg and the mass of the hydroxypropylated lignin is 28 kg.

[0056] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that the mass of the quaternary ammonium salt modifier in Example 7 is 4.5 kg and the mass of the hydroxypropylated lignin is 25.5 kg.

[0057] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that the porogen in Example 8 is p-xylene.

[0058] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that the pore-forming agent in Example 9 is dodecyl alcohol.

[0059] Comparative Example 1 Comparative Example 1 is based on Example 3. The only difference between Comparative Example 1 and Example 3 is that the cationic modified lignin in the resin matrix preparation step of Comparative Example 1 is replaced with hydroxypropylated lignin.

[0060] Comparative Example 2 Comparative Example 2 is based on Example 3. The only difference between Comparative Example 2 and Example 3 is that the activated carbon microspheres are replaced with activated carbon particles in Comparative Example 2.

[0061] Performance testing experiment

[0062] Determination of potassium sorbate content, chloride content, and organic matter content: Using GB1886.39-2015 National Food Safety Standard for Food Additives - Potassium Sorbic Acid - as the standard, the potassium sorbate content was calculated by titration with a standard perchloric acid solution. The sample was weighed into a weighing bottle, dried in an oven, and after cooling, the weight loss of potassium sorbate was determined. The sample was prepared into a solution, and silver nitrate solution was added and mixed thoroughly to prepare a series of standard turbidity solutions of varying concentrations. The turbidity of the sample solution was compared to that of the standard turbidity solutions. The sample solution and formaldehyde standard solution were mixed separately with fuchsin-sulfurous acid solution to prepare a series of standard colorimetric solutions. The colorimetric results were recorded. Each sample was tested three times, and the average value was taken. The results are recorded in Table 1.

[0063] Determination of heavy metal ion content in potassium sorbate: The standard GB 5009.74-2014 National Food Safety Standard Test for Limits of Heavy Metals in Food Additives was selected. The heavy metal ion content in potassium sorbate was detected by inductively coupled plasma mass spectrometry (ICP-MS). Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.

[0064] The national standard for potassium sorbate is recorded in Table 2.

[0065] Table 1. Determination of potassium sorbate, chloride, organic matter and heavy metal ion content Example 1 99.5 0.15 <0.009 <0.06 0.57 0.37 Example 2 99.4 0.13 <0.008 <0.06 0.49 0.31 Example 3 99.7 0.07 <0.007 <0.05 0.35 0.19 Example 4 99.2 0.25 <0.012 <0.07 0.92 0.58 Example 5 99.3 0.23 <0.013 <0.07 0.88 0.49 Example 6 99.2 0.33 <0.014 <0.08 0.97 0.79 Example 7 99.1 0.29 <0.013 <0.07 0.93 0.77 Example 8 98.8 0.59 <0.015 <0.09 1.52 1.12 Example 9 98.6 0.63 <0.016 <0.09 1.59 1.34 Comparative Example 1 98.1 0.89 <0.018 <0.1 2.58 1.77 Comparative Example 2 98.2 0.95 <0.018 <0.1 2.73 1.86 Table 2 Relevant National Standards for Potassium Sorbate

[0066] As shown in Table 1, the potassium sorbate content of Examples 1-3 is greater than 99.4%, the weight loss after drying is less than 0.15%, the chloride content is less than 0.009%, the aldehyde content is less than 0.06%, the arsenic ion content is less than 0.57 mg / kg, and the lead ion content is less than 0.37 mg / kg. This shows that the potassium sorbate prepared in this application has high purity and low impurity content.

[0067] As shown in Table 1, the mass ratio of p-xylene to dodecayl alcohol in Example 4 was 1:0.5, in Example 5 it was 1:2, and in Example 3 it was 1:1.25. In Examples 4 and 5, the potassium sorbate content was greater than 99.2%, the weight loss after drying was less than 0.25%, the chloride content was less than 0.013%, the aldehyde content was less than 0.07%, the arsenic ion content was less than 0.92 mg / kg, and the lead ion content was less than 0.58 mg / kg. In Example 3, the potassium sorbate content was 99.7%, the weight loss after drying was 0.07%, the chloride content was less than 0.007%, and the aldehyde content was... The content of arsenic ions is less than 0.05%, the arsenic ion content is 0.35 mg / kg, and the lead ion content is 0.19 mg / kg. Compared with Example 3, the quality of potassium sorbate product decreased, the drying effect decreased, and the number of impurities increased. This is because the changes in the amount of p-xylene and dodecanol in the pore-forming agent prevent the monomers in the oil or aqueous phase from fully swelling and forming pores. The morphology of the activated carbon microspheres cannot reach an excellent state, the specific surface area and porosity decrease, and the filtration performance of the activated carbon microsphere resin decreases. As a result, the quality of potassium sorbate product decreased, the drying effect decreased, and the number of impurities increased.

[0068] As shown in Table 1, the only difference between Example 6 and Example 3 is that the mass ratio of quaternary ammonium salt modifier to hydroxypropylated lignin in Example 6 is 0.07:1, the potassium sorbate content in Example 6 is 99.2%, the drying weight loss is 0.33%, the chloride content is less than 0.014%, the aldehyde content is less than 0.08%, the arsenic ion content is 0.97 mg / kg, and the lead ion content is 0.79 mg / kg. Compared with Example 3, the quality of potassium sorbate product in Example 6 has decreased, the drying effect has decreased, and the number of impurities has increased. This is because the amount of quaternary ammonium salt modifier is reduced, the positive charge of cationic modified lignin is reduced, the porous structure of activated carbon microsphere resin is reduced, the adsorption of negatively charged impurity ions is reduced, and the hygroscopicity of potassium sorbate product is increased. Therefore, the quality of potassium sorbate product has decreased, the drying effect has deteriorated, and the number of impurities has increased.

[0069] As shown in Table 1, the only difference between Example 7 and Example 3 is that the mass ratio of quaternary ammonium salt modifier to hydroxypropylated lignin in Example 7 is 0.18:1, the potassium sorbate content in Example 7 is 99.1%, the drying weight loss is 0.29%, the chloride content is less than 0.013%, the aldehyde content is less than 0.07%, the arsenic ion content is 0.93 mg / kg, and the lead ion content is 0.77 mg / kg. Compared with Example 3, Example 7 has an increased amount of quaternary ammonium salt modifier, more grafted quaternary ammonium salt groups, and an increased hydrolysis rate of the quaternary ammonium salt groups themselves, resulting in a decrease in cationization efficiency. Consequently, the positive charge of the cationic modified lignin is reduced, the adsorption performance of the activated carbon microsphere resin is decreased, and the quality of the potassium sorbate product is reduced, the drying effect is worse, and the number of impurities is increased.

[0070] As shown in Table 1, in Example 8, the porogen was replaced with p-xylene, and in Example 9, the porogen was replaced with dodecanol. In Example 8, the potassium sorbate content was 98.8%, the drying loss was 0.59%, the chloride content was less than 0.015%, the aldehyde content was less than 0.09%, the arsenic ion content was 1.52 mg / kg, and the lead ion content was 1.12 mg / kg. In Example 9, the potassium sorbate content was 98.6%, the drying loss was 0.63%, the chloride content was less than 0.016%, and the aldehyde content was less than 0.09%. The arsenic ion content was 1.59 mg / kg, and the lead ion content was 1.34 mg / kg. Compared with Example 3, the quality of potassium sorbate product decreased significantly, the drying effect deteriorated, and the number of impurities increased significantly. This is because the binary compound pore-forming agent was replaced with a single pore-forming agent. The single pore-forming agent can only promote the swelling and pore formation of monomers in the oil phase or aqueous phase. The pore structure of the other phase is poor, and the adsorption performance of activated carbon microsphere resin is reduced. Therefore, the quality of potassium sorbate product decreased significantly, the drying effect deteriorated, and the number of impurities increased significantly.

[0071] As shown in Table 1, the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the cationic modified lignin in the resin matrix preparation step was replaced with hydroxypropylated lignin. The potassium sorbate content in Comparative Example 1 was 98.1%, the drying weight loss was 0.89%, the chloride content was less than 0.018%, the aldehyde content was less than 0.1%, the arsenic ion content was 2.58 mg / kg, and the lead ion content was 1.77 mg / kg. Compared with Example 3, the quality of the potassium sorbate product in Comparative Example 1 decreased significantly, the drying effect was worse, and the number of impurities increased significantly. This is because replacing the cationic modified lignin with hydroxypropylated lignin lacks quaternary ammonium salt modification treatment, which reduces the positive charge of the resin matrix, decreases the porous structure of the activated carbon microsphere resin, reduces the specific surface area and porosity, and lowers the adsorption performance. As a result, the quality of the potassium sorbate product decreased significantly, the drying effect was worse, and the number of impurities increased significantly.

[0072] As shown in Table 1, the only difference between Comparative Example 2 and Example 3 is that the activated carbon microspheres in Comparative Example 2 were replaced with activated carbon granules. The potassium sorbate content in Comparative Example 2 was 98.2%, the drying weight loss was 0.95%, the chloride content was less than 0.018%, the aldehyde content was less than 0.1%, the arsenic ion content was 1.59 mg / kg, and the lead ion content was 1.34 mg / kg. Compared with Example 3, the quality of the potassium sorbate product in Comparative Example 2 decreased significantly, the drying effect was worse, and the number of impurities increased significantly. This is because the activated carbon microspheres were replaced with activated carbon granules. The specific surface area and porosity of activated carbon granules are smaller than those of activated carbon microspheres, resulting in poorer adsorption capacity and filtration efficiency. The adsorption performance of the activated carbon microsphere resin also deteriorated, thus leading to a significant decrease in the quality of the potassium sorbate product, a worse drying effect, and a significant increase in the number of impurities.

[0073] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.

Claims

1. A method for continuous composite reaction of potassium sorbate, characterized in that: Includes the following steps: (1) Sorbic acid is dissolved in a solvent to obtain a sorbic acid solution. Potassium hydroxide aqueous solution is added to the sorbic acid solution and stirred to obtain a reaction solution. The pH value of the reaction solution is controlled. After the reaction, potassium sorbate aqueous solution is obtained. (2) Control the temperature of potassium sorbate aqueous solution and filter the potassium sorbate aqueous solution through activated carbon microsphere resin to obtain the filtered potassium sorbate solution. (3) After cooling the filtered potassium sorbate solution, dry it to obtain the finished potassium sorbate product; The activated carbon microsphere resin comprises a resin matrix and activated carbon microspheres, wherein the resin matrix comprises the following components in parts by weight: 10-20 parts of cationic modified lignin 40-50 parts of butyl acrylate 30-40 parts of ethylene glycol dimethacrylate 3-7 parts initiator; The activated carbon microspheres were prepared using the following steps: Polyvinylpyrrolidone, glycidyl methacrylate and azobisisobutyronitrile were mixed to obtain a mixed solution. The mixed solution was sonicated and then inert gas was introduced to remove oxygen. The ultrasonically deoxygenated mixed solution was then rotary evaporated to carry out the reaction. The mixed solution after the reaction was centrifuged to obtain a precipitate. The precipitate was washed and dried to obtain glycidyl methacrylate seed particles. Glycidyl methacrylate seed particles were activated to obtain a seed particle suspension. Glycidyl methacrylate, trimethylolpropane trimethacrylate and a pore-forming agent were mixed to obtain an oil phase. Sodium dodecyl sulfate and polyvinylpyrrolidone were mixed into deionized water to obtain an aqueous phase. The oil phase was added to the aqueous phase and emulsified to obtain an emulsion. Benzoin dimethyl ether and the emulsion were added to the activated seed particle suspension. The mixture was stirred under light-protected conditions to obtain a polymerization solution. The stirred polymerization solution was reacted under ultraviolet light irradiation. The polymer solution was centrifuged and washed to obtain polymer microspheres. The polymer microspheres were carbonized at high temperature to obtain carbonized microspheres. The carbonized microspheres were then heated further and water vapor was introduced to carry out a second carbonization reaction. After cooling, activated carbon microspheres were obtained.

2. The method for continuous composite reaction of potassium sorbate according to claim 1, characterized in that: The cationic modified lignin includes quaternary ammonium salt modifiers and hydroxypropylated lignin.

3. The method for continuous composite reaction of potassium sorbate according to claim 2, characterized in that: The mass ratio of the quaternary ammonium salt modifier to the hydroxypropylated lignin is (0.1-0.15):

1.

4. The method for continuous composite reaction of potassium sorbate according to claim 3, characterized in that: The quaternary ammonium salt modifier includes epichlorohydrin and tetramethylethylenediamine.

5. The method for continuous composite reaction of potassium sorbate according to claim 1, characterized in that: The polymer microspheres are carbonized at a temperature of 300-400℃ for the first time and at a temperature of 600-700℃ for the second time.

6. The method for continuous composite reaction of potassium sorbate according to claim 1, characterized in that: The pore-forming agents are p-xylene and dodecanol.

7. The method for continuous composite reaction of potassium sorbate according to claim 6, characterized in that: The mass ratio of p-xylene to dodecanol is 1:(1-1.5).

8. The method for continuous composite reaction of potassium sorbate according to claim 7, characterized in that: The activated carbon microsphere resin is prepared using the following steps: A mixture of cationic modified lignin, butyl acrylate, ethylene glycol dimethacrylate and an initiator was prepared and reacted under heating and stirring conditions. The reacted mixture was washed and dried to obtain a resin matrix. A spinning solution is obtained by mixing a resin matrix, polyvinylidene fluoride, and polyethylene glycol. Activated carbon microspheres are dispersed in N,N-dimethylformamide to obtain an activated carbon microsphere suspension. The spinning solution and the activated carbon microsphere suspension are then subjected to coaxial electrospinning to obtain activated carbon microsphere resin.

9. The method for continuous composite reaction of potassium sorbate according to claim 1, characterized in that: The temperature for filtration using activated carbon microsphere resin in step (2) is 55-65℃, and the filtration time is 40-60min.

Citation Information

Patent Citations

  • Phenolic resin activated carbon microballon and rapid preparation method thereof

    CN101774577A

  • Preparing method of heavy metal adsorbent lignin microspheres

    CN108940218A